2020
DOI: 10.1002/ldr.3695
|View full text |Cite
|
Sign up to set email alerts
|

Assessing UN indicators of land degradation neutrality and proportion of degraded land for Botswana using remote sensing based national level metrics

Abstract: Achieving land degradation neutrality (LDN) has been proposed as a way to stem the loss of land resources globally. To date, LDN operationalization at the country level has remained a challenge both from a policy and science perspective. Using an approach incorporating cloud-based geospatial computing with machine learning, national level datasets of land cover, land productivity dynamics, and soil organic carbon stocks were developed. Using the example of Botswana, LDN and proportion of degraded land were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
4
15
0
Order By: Relevance
“…This finding is confirmed by several studies highlighting the importance of using high-resolution imagery to detect LD, especially on heterogeneous landscapes, such as KK districts, dominated by heterogenous small-scale farms [50,55,56]. Recent studies that used ground-truth data for validation showed that using Landsat data for the LC sub-indicator captured LD better than using ESA-based 300 m datasets [50]. Nevertheless, certain factors could have impacted the AM, such as the scan-line failure in Landsat ETM+ data.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This finding is confirmed by several studies highlighting the importance of using high-resolution imagery to detect LD, especially on heterogeneous landscapes, such as KK districts, dominated by heterogenous small-scale farms [50,55,56]. Recent studies that used ground-truth data for validation showed that using Landsat data for the LC sub-indicator captured LD better than using ESA-based 300 m datasets [50]. Nevertheless, certain factors could have impacted the AM, such as the scan-line failure in Landsat ETM+ data.…”
Section: Discussionsupporting
confidence: 76%
“…The resulting differences between LD estimates based on DM and AM were striking and could be primarily attributed to the difference in the pixel size of 6.25 ha (MODIS) versus 0.09 ha (Landsat), which could be critical in specific areas where fine LD patterns prevailed. This finding is confirmed by several studies highlighting the importance of using high-resolution imagery to detect LD, especially on heterogeneous landscapes, such as KK districts, dominated by heterogenous small-scale farms [50,55,56]. Recent studies that used ground-truth data for validation showed that using Landsat data for the LC sub-indicator captured LD better than using ESA-based 300 m datasets [50].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We conducted the widely used Mann-Kendall (MK) test method (Akinyemi, Ghazaryan, & Dubovyk, 2020;Gichenje & Godinho, 2018;Touré et al, 2020) to test the significance of the long-term trends in time series. In the MK trend test, the original hypothesis H o is that there are no trends; the alternative hypothesis is that there is a trend that could either be negative, positive, or nonnull (Mann, 1945).…”
Section: Mann-kendall Testmentioning
confidence: 99%
“…These datasets are a consistent series of multi-sensor annual maps from 1992 to 2018 [34]. The land categories in the ESA-LC were aggregated into six categories for compatibility with previous studies in Botswana [35]-tree-covered areas, grassland, cropland, water bodies, artificial surfaces (settlement including infrastructure) and otherland (Table S2). Tree-covered areas comprise forests and woodlands.…”
Section: Data Sourcesmentioning
confidence: 99%